Impacts of the preceding cancer-specific health-related quality of life instruments on the responses to the subsequent EQ-5D-5L - Shoki Izumi; Yasuhiro Hagiwara; Yutaka Matsuyama; Takeru Shiroiwa; Naruto Taira; Takuya Kawahara; Keiko Konomura; Shinichi Noto; Takashi Fukuda; Kojiro Shimozuma (Health and Quality of Life Outcomes, 2023)
Abstract Background In clinical studies, the EQ-5D-5L is often employed with disease-specific health-related quality of life instruments. The questions in the former are more general than the latter; however, it is known that responses to general questions can be influenced by preceding specific questions. Thus, the responses to the EQ-5D-5L have the possibility of being influenced by the preceding disease-specific health-related quality of life instruments. This may lead to bias in the cost-effectiveness analysis results. Therefore, this study aimed to evaluate the impact of the preceding cancer-specific health-related quality of life instruments on the EQ-5D-5L responses. Methods We prepared questionnaire booklets containing the EQ-5D-5L, the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30, and the Functional Assessment of Cancer Therapy General with different orders. Using a quasi-randomized design, they were distributed to the patients undergoing drug therapy for advanced cancer, who were classified into three groups: Groups 1, 2, and 3 (the EQ-5D-5L placed first, second, and last, respectively). We compared the EQ-5D-5L index and the missingness of EQ-5D-5L among the groups. Results The mean EQ-5D-5L index was 0.796, 0.760, and 0.789 for groups 1 (n = 300), 2 (n = 306), and 3 (n = 331), respectively. The difference between Groups 2 and 1 was − 0.036 (95% CI − 0.065 to − 0.007; p = 0.015). The proportion of patients with an incomplete EQ-5D-5L was 0.11, 0.11, and 0.05 for Groups 1, 2, and 3, respectively. The difference of the proportions between group 3 and 1 and between 3 and 2 was − 0.06 (95% CI − 0.10 to − 0.02; p = 0.003) and − 0.06 (95% CI − 0.10 to − 0.02; p = 0.003), respectively. Conclusions Although the EQ-5D-5L index differed according to the instrument orders, the difference size would not be considerably larger than the minimally important difference. The patients tended to complete the EQ-5D-5L when they were placed at the end of the questionnaire.